2021
DOI: 10.3390/pathogens10081062
|View full text |Cite
|
Sign up to set email alerts
|

Murine Models of Central Nervous System Disease following Congenital Human Cytomegalovirus Infections

Abstract: Human cytomegalovirus infection of the developing fetus is a leading cause of neurodevelopmental disorders in infants and children, leading to long-term neurological sequela in a significant number of infected children. Current understanding of the neuropathogenesis of this intrauterine infection is limited because of the complexity of this infection, which includes maternal immunological responses that are overlaid on virus replication in the CNS during neurodevelopment. Furthermore, available data from human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 90 publications
(189 reference statements)
1
8
0
Order By: Relevance
“…Since MCMV, in contrast to HCMV, does not cross the placenta, different approaches to infection are used to model congenital CMV infection in mice, including inoculation of MCMV into the placenta, intracerebral or intraventricular inoculation of virus in fetal or newborn mice, and intravenous and intraperitoneal injection of newborn mice (Moulden et al., 2021). Although these models do not entirely recapitulate all aspects of the human congenital CMV infection, they have been instrumental in extending our understanding of the neuropathogenesis of congenital HCMV infection.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Since MCMV, in contrast to HCMV, does not cross the placenta, different approaches to infection are used to model congenital CMV infection in mice, including inoculation of MCMV into the placenta, intracerebral or intraventricular inoculation of virus in fetal or newborn mice, and intravenous and intraperitoneal injection of newborn mice (Moulden et al., 2021). Although these models do not entirely recapitulate all aspects of the human congenital CMV infection, they have been instrumental in extending our understanding of the neuropathogenesis of congenital HCMV infection.…”
Section: Commentarymentioning
confidence: 99%
“…inoculation of MCMV results in the establishment of systemic infection during which the virus enters different organs, including those of the central nervous system (CNS). This approach is useful for studying different aspects of the pathogenesis of congenital CMV infection, including immune response and mechanisms of pathohistological and neurological damage such as hearing loss and impairment of motor coordination (Moulden, Sung, Brizic, Jonjic, & Britt, 2021;Slavujica et al, 2015). 1.…”
Section: Infection Of Newborn Mice With MCMV To Model Congenital Cmv ...mentioning
confidence: 99%
“…Following infection, MCMV infects peripheral organs and subsequently spreads hematogenously to the CNS. Although this model does not recapitulate in utero transmission of the virus, it takes advantage of results from previous studies that have shown that the newborn mouse is neurodevelopmentally similar to a late 2nd trimester human fetus (Bortolussi et al, 2014; Moulden et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Because HCMV is known as the “silent pandemic,” it is vital to use as many available resources to determine the mechanistic causes for the clinical manifestations that have been observed. Murine models are a great tool for adding to this field of study ( Tsutsui et al., 2008 ; Moulden et al., 2021 ; Slavuljica et al., 2015 ). Due to the species specificity of HCMV (i.e., HCMV can only productively infect humans), animal models for direct HCMV infection are lacking to study HCMV pathogenesis.…”
mentioning
confidence: 99%
“…Hearing loss as a result of cHCMV is highly complex, and not just solely involving the central nervous system (CNS) anomalies. Furthermore, clinical manifestation of hearing loss can be variable and can include presentations such as delayed onset hearing loss, unilateral hearing loss, and progressive hearing loss post infection ( Moulden et al., 2021 ). Week 7–8 mice demonstrated significant hearing loss following infection with MCMV at E13.5 ( Zhou et al., 2022 ).…”
mentioning
confidence: 99%